(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Beam bridges are the simplest and oldest type of bridge in use today, and are a popular type. A truss bridge is a bridge whose load-bearing superstructure is composed of a truss.Various types of different design of truss structure are constructed in bridges depending upon the type of bridge and volume of vehicles passing through it. This research work comprises of design and analysis of different types of bridge structure for railway systems. The different trusses are made from the steel material and a comparative study is done based on the results. For the study four type of truss design is taken in to consideration such as rectangular truss, X-type, V-type, and K-type truss. The results are calculated using Staad Pro. Software and the values are observed. The results are compared based on support reaction, displacement, shear force and torsion. Both maximum and minimum values for all the respective cases have been depicted in the work including cost analysis.